2018
DOI: 10.1680/jcoma.16.00009
|View full text |Cite
|
Sign up to set email alerts
|

Influencing compressive strength of roller-compacted concrete

Abstract: Roller-compacted concrete is a type of zero-slump concrete that usually has a higher compressive strength than ordinary concrete, with the same cement content. This is primarily due to the high level of aggregate interlock achieved by compaction, but many other factors are also involved. The goal of this study was to investigate the influence of aggregate gradation, cement content, water content, compaction effort, curing conditions and admixtures on the compressive strength of roller-compacted concrete. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…For example, Brazil can use RCC with RCA as a material for pavements or sub-base pavements to mitigate problems from infrastructure highways [1,2]. On the other hand, some recognized benefits of RCC in pavements are cost-effectiveness, faster construction, environmental friendliness, and high-level performance [12][13][14][15][16]. RCC is a zero-slump concrete used for hydraulic and paving construction sites in civil engineering.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Brazil can use RCC with RCA as a material for pavements or sub-base pavements to mitigate problems from infrastructure highways [1,2]. On the other hand, some recognized benefits of RCC in pavements are cost-effectiveness, faster construction, environmental friendliness, and high-level performance [12][13][14][15][16]. RCC is a zero-slump concrete used for hydraulic and paving construction sites in civil engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the percentage of aggregates in mixtures is around 80%. It proves that aggregates are vital for producing this type of concrete [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] presented a stepwise mixture design methodology for aggregate proportioning and particle-size distribution of combined aggregates which may secure high packing density and lead to enhanced performance of RCC mixture. [11], assessed the influence of aggregate gradation, curing conditions, cement dosage, water content, and chemical additives on RCC characteristics. It also indicated that 98% compaction degree with respect to modified proctor compaction, could be reached to attain higher compressive strength values.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently placement is by roller compaction, with applications for pavements and mass concrete dam construction. In their study Chhorn and Lee (2018) have focussed on the influence of constituent material properties and proportions on compressive strength performance. A variety of mixes were prepared in the laboratory and strength properties measured at 3, 7, 28 and 56 days.…”
mentioning
confidence: 99%